Electron induced modification of the surface electrochemical properties of diamond electrodes - Goeting, C; Marken, F; Salter, C; Compton, R; Foord, J (1999)
A novel method has been developed to modify the surface properties of boron-doped CVD diamond electrodes by electron stimulated desorption (ESD) of hydrogen and oxygen from as grown diamond surfaces allowing the selective electrochemical silver deposition on the areas not irradiated with electrons.